Insulin-like growth factor 1 receptor (IGF-1R) as a target of MiR-497 and plasma IGF-1R levels associated with TNM stage of pancreatic cancer. - Jian-Wei Xu (Public Library of Science (PLoS), 2014)
The expression levels and regulatory roles of miR-497 in pancreatic cancer are unclear. The clinical value of plasma insulin-like growth factor 1 receptor (IGF-1R) in pancreatic cancers has not been investigated. In the present study, we demonstrated that miR-497 was significantly downregulated in pancreatic cancer tissues. Upregulation of miR-497 in BxPC-3 and AsPC-1 pancreatic cancer cell lines inhibited proliferation, enhanced apoptosis, re-sensitized cells to gemcitabine and suppressed IGF-1R and p-AKT expression through direct downregulation of IGF-1R protein expression. Opposite effects were observed after downregulation of miR-497. Plasma IGF-1R levels in patients with pancreatic cancer increased significantly, compared with that in patients with chronic pancreatitis, other pancreatic tumors and pancreatic neuroendocrine tumors (P = 0.006, P = 0.018 and P = 0.004, respectively), and displayed potential values for distinguishing pancreatic lesions. However, the levels in pancreatic cancer patients were comparable to that in healthy volunteers (P = 0.095). The tumor locations and TNM stage were associated with plasma IGF-1R levels (P = 0.013 and P = 0.01, respectively). There was no significant difference of overall survival between high and low IGF-1R expression groups. In conclusion, we demonstrated that miR-497 attenuated the malignancy of pancreatic cancer cells and promoted sensitivity of cells to gemcitabine by directly downregulation of IGF-1R expression. Plasma IGF-1R displayed a potential value for distinguishing pancreatic lesions and could be a new biomarker for guiding TNM stage of pancreatic cancer.